2021
DOI: 10.1111/joa.13450
|View full text |Cite
|
Sign up to set email alerts
|

The influence of castration on intramural neurons of the urinary bladder trigone in male pigs

Abstract: The present study investigated the influence of castration performed at neonatal age on neuronal elements in the intramural ganglia of the urinary bladder trigone (UBT) in male pigs using double‐labeling immunohistochemistry. The ganglia were examined in intact (IP) 7‐day‐old (castration day) pigs, and at 3 and 6 months after surgery. In IP and control (3‐ and 6‐month‐old noncastrated pigs) groups, virtually, all neurons were adrenergic (68%) or cholinergic (32%) in nature. Many of them (32%, 51%, and 81%, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…In both cases, they are "mixed" autonomic ganglia consisting of either sympathetic adrenergic or parasympathetic cholinergic neurons. Recent investigations of Kaleczyc et al [12] and earlier findings [61], which have revealed that the vast majority of UBT intramural neurons in male pigs are either adrenergic or cholinergic in nature, seem to further confirm this concept. No wonder then that changes in percentages of adrenergic and cholinergic neurons observed after castration [12] were similar to those found in the APG.…”
Section: Effect Of Castration On the Chemical Coding Of Peripheral Neurons Supplying Male Urogenital Tractmentioning
confidence: 71%
See 4 more Smart Citations
“…In both cases, they are "mixed" autonomic ganglia consisting of either sympathetic adrenergic or parasympathetic cholinergic neurons. Recent investigations of Kaleczyc et al [12] and earlier findings [61], which have revealed that the vast majority of UBT intramural neurons in male pigs are either adrenergic or cholinergic in nature, seem to further confirm this concept. No wonder then that changes in percentages of adrenergic and cholinergic neurons observed after castration [12] were similar to those found in the APG.…”
Section: Effect Of Castration On the Chemical Coding Of Peripheral Neurons Supplying Male Urogenital Tractmentioning
confidence: 71%
“…Recent investigations of Kaleczyc et al [12] and earlier findings [61], which have revealed that the vast majority of UBT intramural neurons in male pigs are either adrenergic or cholinergic in nature, seem to further confirm this concept. No wonder then that changes in percentages of adrenergic and cholinergic neurons observed after castration [12] were similar to those found in the APG. In the 3-and 6-month-old castrated male pigs, the percentages of adrenergic and cholinergic neurons were comparable (41% and 39%, and 58% and 58%, respectively) but they differed significantly from those determined in the non-castrated animals of the same age (68% and 68%, and 31% and 31%, respectively).…”
Section: Effect Of Castration On the Chemical Coding Of Peripheral Neurons Supplying Male Urogenital Tractmentioning
confidence: 71%
See 3 more Smart Citations